An international network (PlaNet) to evaluate a human placental testing platform for chemicals safety testing in pregnancy - Brownbill, Paul; Chernyavsky, Igor; Bottalico, Barbara; Desoye, Gernot; Hansson, Stefan; Kenna, Gerry; Knudsen, Lisbeth E.; Markert, Udo R.; Powles-Glover, Nicola; Schneider, Henning; Leach, Lopa (Elsevier, 2016)
tThe human placenta is a critical life-support system that nourishes and protects a rapidly growing fetus; aunique organ, species specific in structure and function. We consider the pressing challenge of providingadditional advice on the safety of prescription medicines and environmental exposures in pregnancy andhow ex vivo and in vitro human placental models might be advanced to reproducible human placentaltest systems (HPTSs), refining a weight of evidence to the guidance given around compound risk assess-ment during pregnancy. The placental pharmacokinetics of xenobiotic transfer, dysregulated placentalfunction in pregnancy-related pathologies and influx/efflux transporter polymorphisms are a few caveatsthat could be addressed by HPTSs, not the specific focus of current mammalian reproductive toxicologysystems. An international consortium, “PlaNet”, will bridge academia, industry and regulators to con-sider screen ability and standardisation issues surrounding these models, with proven reproducibilityfor introduction into industrial and clinical practice.